Estudo e caracterização físico-química de sistemas supramoleculares nanoagregados e de matrizes poliméricas associadas à ciclodextrina - Frederico Barros de Sousa (2010)
Herein, supramolecular systems involving beta-cyclodextrin and polymer matrix were prepared and characterized. More specifically, the host-guest system formed between beta-cyclodextrin and BPP10c, a bradykinin potentiating peptide with antihypertensive action, was studied. Additionally, the beta-cyclodextrin self-assembly was investigated, as well as, the influence of the Ampicillin (AMP), a broad spectrum antibiotic highly water soluble, in the self-assembly process. Moreover, thephotochromic properties of the modified beta-cyclodextrin and the PMAA polymer with spiropyran were studied looking forward their application as support for cellular growth. Combining the nuclear resonance magnetic and isothermal titration calorimetry results, the supramolecular interactions between BPP10c and AMP with beta-CD were obtained. Thethermodynamic inclusion parameters for these supramolecular systems indicated the spontaneity of the inclusion process. In addition, for the beta-CD:AMP supramolecular system, these results indicated that different stoichiometries can exist simultaneously in solution, which was not observed for the beta-CD:BPP10 system, since only one binding site was observed between these molecules. The FTIR-ATR and circular dichroism results demonstrated that the beta-CD:BPP10c interactionwas not able to modify significantly the peptide secondary structure, however, the AMP molecule was capable to change the supramolecular arrange of the beta-CD aggregates, indicating the dependence between beta-CD concentration and the aggregate arrange. Molecular dynamics simulation allowed proposing the tridimensional structure for the beta-CD aggregates and these complexes, are in agreement with the experimental finds. The photochromic materials synthesized in this work based on spiropyran molecule presented reverse photochromism and it was also observed that their isomerization rates depend on the microenvironment around the spiropyran molecule. In this sense, the beta-CD[ind]sp molecule presented the fastest isomerization rate comparing to the other materials synthesized, PMAASP andPMAA-beta-CDSP. The PMAA-beta-CD[ind]sp electrospun nanofibers surface was more hydrophobic than those nanofibers obtained from PMAA polymer. Moreover, this hydrophobicity observed for thePMAA-beta-CD[ind]sp was light dependent, indicating the presence of the spiropyran on the mats surface.